MENTORIA E CULTURA ORGANIZACIONAL: UM ESTUDO DE CASO NA ORGANIZAÇÃO PERFORMANCE AUDITORIA E CONSULTORIA EMPRESARIAL - Oliveira Neto, Constantino de Carvalho (2012)
Knowledge is the most important resource of an organization. Thereby, the organizational learning becomes an essential process for companies who wish to remain in a highly competitive market. Thus, the social-practice learning programs offer the opportunity to efficiently and completely socialize knowledge. Among the possibilities of these programs, we highlight in this work the mentoring: a form of social-practice learning whereby a more experienced person is offering his apprentice psychosocial support, professional support and a role modeling. Besides it shows a broad overview of the subject, this work makes a theoretical review of the different types of mentoring as its characteristics and benefits. From this point, it also tries to identify which organizational cultural values are important for the mentoring to be successful. In order to identify the representation of the prevalent thoughts, and consequently the culture values e believes, this work makes use of simple case study with an auditing and consulting company Performance and the methodology of the collective subject discourse (DSC). As a result, this work finds different types of mentoring that occurs inside the Performance, based on a review of major studies in the literature. Moreover, it was observed that seven cultural values are dominant among the professionals in the organization. Thus, were identified three different categories of values that are fundamental to success of the mentoring relationships.